(untitled) (Journal of Hama University, 2020)
This study was carried out to investigate the incidence of Aspergillus fumigatus infections in the broiler houses in the middle region of Syria. Results showed that seventy two out of 240 (30%) of air samples from 20 broiler chicken houses were positive for Aspergillus fumigatus by culturing on sabouraud agar. Results showed that eighty out of 305 (26.23%) lungs and air sacs samples from 26 broiler chicken flocks were positive for Aspergillus fumigatus. Gross lesions were observed in lungs and air sacs at postmortem examination. Small white nodular lesions were observed in the congested lungs and air sacs. Aspergillus fumigatus was cultured on sabouraud agar. White colonies were seen, at first, which turned dark green to grayish later. It was observed that Infection was higher in birds of less than two weeks of age with percentage of 71% comparing with older birds with percentage of 29%.